Macroeconomic Digital Book Development: How are the Feasibility of Experts and Student Responses? - Muslim, Fachruddiansyah; Refnida, Refnida; Chen, Diki; Wirayuda, Ricky Purnama (Journal of Education Technology, 2021)
The use of books today is inseparable from the rapid development of technology, one of the book developments that attracts a lot of interest from teachers is digital books. Digital books themselves are very suitable for complex and memorizing learning such as macroeconomics courses, the reason digital books are suitable for macroeconomic learning is that they can be carried anytime and anywhere. This study aims to see the feasibility of the product being developed, namely a digital book on macroeconomic material. The feasibility of the digital book made is divided into two, namely the feasibility of the experts and the feasibility of the sample (students). This research is an R&D type with the selected development model, namely the ADDIE development model. The sampling technique used is simple random sampling with a sample of 36 active students of economic education study program. There are 3 data collection instruments used including media and material expert validation instruments which have 10 statements and student response instruments totaling 28 statements. Analysis of the data used in the form of descriptive statistics. The results of material validation for both validators were 42 (very good) and 37 (good), then for media experts, a score of 38 (good) and 39 (good), while for student responses to the material aspect, a score of 29.25 (worth it) was obtained. , media aspect is 52.5 (very worth it), output aspect is 9.75 (worth it), and for all aspects is 91.5 (very worth it). Based on the results that have been obtained from the validation and small group trials, it shows that digital books on macroeconomic material are appropriate to be used as complementary learning resources in macroeconomics lectures.